ANALISIS SIRKULASI POLA TATA RUANG PADA BANGUNAN SEAWORLD ANCOL JAKARTA UTARA (Studi Kasus : Seaworld, Jakarta Utara - Faturokhman, Irfan; Amelia, Siska (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
SeaWorld Ancol is an oceanarium located in Taman Impian Jaya Ancol. Functionalapproach, according to the sequence of attractions presented. Lay out the space by making good useof the space that occurs and adapting to the circular shape of the building. The rows of columns andthe semicircular shape of the building are the limiting factors of the design. The semi-circle shape,according to Heryani, is related to visitor traffic and flexibility in arranging the exhibition area.The research uses a qualitative descriptive method by conducting research directly into thefield and research data collection then researchers will analyze the Spatial Patterns at Seaworld in theAncol Area, North Jakarta. The results of the discussion and research show that the application of theelements of spatial patterns and relationships in the Seaworld building is in accordance with existingtheories